SURVIVAL AND GROWTH OF MILKFISH (Chanos chanos) LARVAE UNDER DIFFERENT COLOUR VALUES OF ORANGE - Taufik Ahmad; Titiek Aslianti (Indonesian Fisheries Research Journal, 1997)
An orange painted tank was proved to be suitable for rearing milkfish larvae, However, light intensity was suspected to affect the suitability such tanks.